2010
DOI: 10.1111/j.1476-5381.2009.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoxia modifies cAMP levels induced by inhibitors of phosphodiesterase‐4 in rat carotid bodies, carotid arteries and superior cervical ganglia

Abstract: Background and purpose: Phosphodiesterase (PDE) inhibitors are useful to treat hypoxia-related diseases and are used in experiments studying the effects of oxygen on 3′-5′-cyclic adenosine monophosphate (cAMP) production. We studied the effects of acute hypoxia on cAMP accumulation induced by PDE inhibitors in oxygen-specific chemosensors, the carotid bodies (CBs) and in non-chemosensitive CB-related structures: carotid arteries (CAs) and superior cervical ganglia (SCG). Experimental approach: Concentration-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
3
13
0
1
Order By: Relevance
“…This finding adds to the literature by identifying PDE3 isoforms in this ganglion and is consistent with previous reports that characterize PDE4 by the effects of their specific inhibitors (Giorgi et al 1994; Lakics et al 2010; Li and Horn 2006; Nunes et al 2010). We found that PDE3a, PDE4b and PDE4d were the most abundant isoforms in the SCG.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding adds to the literature by identifying PDE3 isoforms in this ganglion and is consistent with previous reports that characterize PDE4 by the effects of their specific inhibitors (Giorgi et al 1994; Lakics et al 2010; Li and Horn 2006; Nunes et al 2010). We found that PDE3a, PDE4b and PDE4d were the most abundant isoforms in the SCG.…”
Section: Discussionsupporting
confidence: 92%
“…We have recently observed that acute hypoxia decreased cAMP levels induced by PDE inhibitors in these ganglia, an opposite effect to that observed in the CB (Nunes et al 2010). …”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Полученные результаты свидетельствуют, что активация аденилатциклазной системы посредством β-адреномиметика, форсколина, IBMX c последующим увеличением внутриклеточного содержания цАМФ приводят к подавлению активирующего действия гипоксии на параметры ýлектрической и, в большей степени, констрикторной активности ГМК мочеточника морской свинки. Согласно литературным данным, активация цАМФ-зависимого сигнального пути, с одной стороны, связана с повышением калиевой проводимости мембраны гладких мышц [2], а с другойуменьшением цитоплазматической концентрации ионов Са 2+ вследствие активации кальциевых насосов плазмалеммы, саркоплазматического ретикулума и (или) натрий-кальциевого обмена в ГМК [3,11].…”
Section: Discussionunclassified
“…When PO 2 diminishes in the internal milieu bathing chemoreceptor cells, the molecular putative O 2 -sensor(s), through ill-defi ned coupling mechanisms, diminish the opening probability of diverse O 2 -sensitive K + channels leading to cell depolarization, activation of voltage operated Ca 2+ channels, entry of Ca 2+ and triggering of the release of several neurotransmitters which, in addition to activating the sensory nerve endings of the CSN, feedback control chemoreceptor cell activity via autoreceptors (Gonzalez et al 1994 ;Conde et al 2009 ;Nurse 2010 ). At every step from O 2 -sensing to the release of neurotransmitters, there are second messengers which fi ne shape the exocytosis and other neurotransmitter releasing mechanisms, and therefore the level of activity generated in the CSN (e.g., Pérez-García et al 1990, 1991Gómez-Niño et al 1994a , b ;Rocher et al 2009 ;He et al 2007 ;Nunes et al 2010 ;Kemp and Telezhkin 2014 ). Among these second messengers there is one, namely hydrogen sulfi de, whose potential capacity to modulate chemoreceptor activity, mechanisms of action, and physiological signifi cance are not well defi ned (Anichkov and Belen'kii 1963 ;Telezhkin et al 2009 ;Li et al 2010 ;Peng et al 2010 ;Fitzgerald et al 2011 ;Olson 2011 ;Haouzi et al 2011 ;Buckler 2012 ;Makarenko et al 2012 ;Kemp and Telezhkin 2014 ).…”
Section: Introductionmentioning
confidence: 98%